2021
DOI: 10.1007/s00520-021-06436-x
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Quality nutrition care is integral to the Oncology Care Model

Abstract: The Oncology Care Model (OCM) is a US Centers for Medicare & Medicaid Services (CMS) specialty model implemented in 2016, to provide higher quality, more highly coordinated oncology care at the same or lower costs. Under the OCM, oncology clinics enter into payment arrangements that include financial and performance accountability for patients receiving chemotherapy treatment. In addition, OCM clinics commit to providing enhanced services to Medicare beneficiaries, including care coordination, navigation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Despite this scientifically verified knowledge, summarized in the European Society for Parenteral and Enteral Nutrition (ESPEN) guidelines on nutrition in cancer patients [2], there is a need for improvement, as cancer-related risk of malnutrition is still too often not assessed [7] and, therefore not noticed early enough by health professionals, is overlooked or not treated adequately [4]. A recent survey found that up to 43% of clinicians (dietetic, nursing, medical) have limited or no confidence in their ability to detect malnutrition and sarcopenia [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this scientifically verified knowledge, summarized in the European Society for Parenteral and Enteral Nutrition (ESPEN) guidelines on nutrition in cancer patients [2], there is a need for improvement, as cancer-related risk of malnutrition is still too often not assessed [7] and, therefore not noticed early enough by health professionals, is overlooked or not treated adequately [4]. A recent survey found that up to 43% of clinicians (dietetic, nursing, medical) have limited or no confidence in their ability to detect malnutrition and sarcopenia [8].…”
Section: Introductionmentioning
confidence: 99%